Aedes mosquito collection and record at Universiti Putra Malaysia, Serdang and potential of jumping spider as predator - Maimusa, Alhaji Hamesu (2011)
The study was conducted in two parts. The first part was on abundance of Aedes mosquitoes at Agricultural Conservatory Park (ACP) of Universiti Putra Malaysia (UPM) and its surrounding areas that include Pine Plantation, Rubber Plantation and Faculty of Design and Architecture, from January to September, 2010. Larvitrap method was used to study the population of Aedes larvae and eggs. Twenty ovitraps were set at predetermined spots in each location and collected after five days on alternating week basis. Larvitrap density Index (LTDI) (number of larvae per trap/number of trap/positive trap x 100%)), larval density (mean number of larvae per ovitrap) and eggs density (egg/paddle) for all study sites were compared using SPSS v. 17. Climatic conditions such as rainfall, temperature and relative humidity of the sites were also recorded. The LTDI showed that, the abundance of Aedes ranged from 26.50% - 98.42% and the larval density ranged from 5.20 ± 2.63 – 19.50 ± 2.80; while the eggs density ranged from 2.95 ± 1.67 - 20.05 ± 4.65. There was no significant difference in both larval and egg populations between the first three sites (p > 0.05). However, there was significant difference between Faculty of Design and Architecture and the other three sites (p < 0.05). The studies indicated significant correlation between LTDI, larval density and eggs density in all the four sites. The study also indicated significant correlation between Aedes population with rainfall (r = 0.796, p < 0.01); while the relationship between the Aedes population with temperature was weak (r = -0.409, p < 0.01). The correlation was also significant between Aedes population with relative humidity (r = 0.546, p < 0.01). The population showed downward trend from January, 2010 and reaches its lowest point sometimes in March, 2010 before it rise again and attained its peak around July and August, 2010 after which it showed another downward trend again. Both the LTDI and larval density showed almost identical trend and had also shown significant correlation. No Aedes aegypti mosquitoes were captured in the study areas. The duration of larval development of Ae. albopictus at UPM Agricultural Conservatory Park was 11.9 ± 0.54; at Rubber Plantatio 10.8 ± 0.74; Pine Plantation 11.4 ± 0.68 and Faculty of Design and Arcitecture 12.7 ± 0.82. The second part of the study was on collection and recording species of spiders in the same study areas and prey preference test. Collection was done based on man’s effort method (number of individual collected per man per hour). Total of eight species from five families were collected. These include four species (Plexippus petersi, Evarcha flavocincta, Viciria pavesii and Hasarius adansoni) from the family Salticidae; Tetragnatha mandibulata from the family Tetragnathidae; Chryosso species from the family Theridiidae;Oxyopes species from the family Oxyopidae and lastly, Cyrtophora beccarii from the family Araneidae. Two species of Salticidae, Plexippus petersi and Evarcha flavocincta were chosen for a test of prey preference. The test spiders were maintained in captivity on diet of early stage larvae of Tenebrio molitor (mealworm beetle) and midges, Chironomus sp. For testing, adult mosquito species (Aedes albopictus), fruit flies (Drosophila melanogaster) and rice weevil (Sitophilus oryzae) were used as prey. Two types of tests using living prey were employed, i.e.simultaneous-presentation tests (two types of prey provided at the same time) and alternate-day tests (different types of prey provided on successive days). Analysis by Chi-square t-Test Goodness of Fit and Mc Nemar test with level of significance at α = 0.05 revealed that, well-fed (last meal 7 days before testing) and starved (last meal 14 days before testing) test spiders of each species took Ae. Albopictus mosquito more often than other insects in both alternate-day and simultaneous-presentation tests (p < 0.05). It was found that, the preference of Plexippus petersi for Ae. albopictus mosquito over other insects offered is weaker than that of Evarcha flavocincta. There was similar preference by both test spiders when well-fed and starved. Ae. albopictus was observed to predominate over Ae. aegypti as the later was not found in either of the study sites. The two species of spider (Plexippus petersi and Evarcha flavocincta) found to be potential predators of Ae. albopictus mosquitoes.